Rights of Assembly and Association - Domaniczky, Endre (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
This study presents the rules of the European Convention on Human Rights (ECHR), which are the European standard for the regulation of the rights of association and assembly. ECHR served as an important model for the Central European states to develop their national legislation during the regime change. The study presents the essence of the rules by interpreting the text of the Convention in its grammatical sense and outlines the limits of the rules based on the case law of the Strasbourg Court of Human Rights. The analysis of the case-law reveals that the Central European framework is divided into several smaller regions, where minority rights and religious issues still play a significant role, and their exercise is often closely linked to the exercise of the rights of association and assembly. Further, the study not only focuses on the past and the present but seeks to illustrate the likely trends in future legal developments. Keywords: right of association, right of assembly, Strasbourg Court, human rights, Central Europe